If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8y + -2x + -1y = 0 Reorder the terms: 6x + -2x + 8y + -1y = 0 Combine like terms: 6x + -2x = 4x 4x + 8y + -1y = 0 Combine like terms: 8y + -1y = 7y 4x + 7y = 0 Solving 4x + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 4x + 7y + -7y = 0 + -7y Combine like terms: 7y + -7y = 0 4x + 0 = 0 + -7y 4x = 0 + -7y Remove the zero: 4x = -7y Divide each side by '4'. x = -1.75y Simplifying x = -1.75y
| 3/4=87*9 | | 7x-12-2x=7x-9 | | (x-1)+(2x+3)+(2x+3)=180 | | 9=87/3/4 | | 15x-.75=13x-.50 | | 87=3/4/9 | | 15x/2+19=12x+7/2 | | 14/19/11 | | 9x^4-10x^2+1=0 | | 1(t-3)+7t=4(2t+4)-13 | | x=0.40(x+15) | | 76c=828 | | y-5=-1/8x | | 7x+3y=5 | | 196*47/49*1/16 | | p-r=c | | 20+15x/2=21 | | 2(5-n)=-25 | | 5/7x=30 | | x+2x+2=10 | | 5/2+5/2y=2y-4 | | 6-2(3x-5)=-8 | | 14+8x=55 | | w=-r | | 12x-170=4x-10 | | 11x-2(x-7)=9(x+1)+7 | | a^2-13a+22=0 | | 7t=4*49 | | 5-9x=-173 | | x+2x+1=10 | | (n-5)*9=54 | | 9(x-1)-3=6x+3(-3+x) |